Health Examination and Training on Making Eco-Enzyme-Based Natural Pesticide as a Solution to Reduce Exposure to Chemical Pesticides - Noviana Dewi; Indah Tri Susilowati; Didik Wahyudi; Anggit Dyah Kusumastuti; Annisa Indah Mutiarasari; Regita Agnesya Putri; Revana Putri Santoso; Septiana Wahyu Wulandari; Zulfi Maulita Fanani; Dida Aulia Arahmanda (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Exposure to pesticides increases the risk of oxidative stress, which triggers inflammation and thereby impairs organ function and metabolic processes, manifesting as abnormalities in blood pressure, hemoglobin levels, total cholesterol, and BMI. This initiative aims to promote sustainable agriculture through training in the production of eco-enzymes as an environmentally friendly pesticide made from household organic waste. The target participants are 30 housewives who are the wives of farmers. Results of clinical examination analysis showed that all participants had at least one risk factor contributing to cardiovascular and metabolic risk factors associated with oxidative stress, with the largest distribution falling into the moderate-risk category (56.7%) and high-risk category (30.0%). Based on the Wilcoxon test, an Asymp. Sig. (2-tailed) p < 0.05 and Z -5,477 was obtained, indicating a significant difference between pre-test and post-test results, showing a significant improvement in scores following the educational intervention. The results of the questionnaire validity test showed a Pearson product-moment correlation of 0.523–0.921, and the reliability test yielded a Cronbach’s alpha of 0.885. The average score from the satisfaction questionnaire completed by the participants was 4.8, indicating a very high level of satisfaction.